PENGARUH MIKORIZA DAN UMUR BENIH TERHADAP DERAJAT INFEKSI, SERAPAN P, PERTUMBUHAN DAN HASIL PADI (Oryza sativa L.) DENGAN METODA SRI (System of Rice Intensification) - Fitriyah, Endah (Majalah Ilmiah SOLUSI, 2012)
This objective of this experiment was to study the effect of Arbuscular Mycorrhizal Fungi inoculant interaction and age of seeds to increase the degree of AMF infection in roots of plants, P uptake, growth and yield of Rice (Oryza sativa L.) using the method of SRI (System of Rice Intensification). Experiments carried out in the garden experiment Rice Research Institute Sukamandi Subdistrict Subang, District West Java, from March 2009 until August 2009. The design environment used in this study were randomized block design with factorial pattern. The first factor was the inoculation of mycorrhizal (M) with two levels: without inoculation of AMF (m0) and AMF inoculant 100 g kg-1 soil (m1). The second factor is the age of rice seed (U) consisting of tree levels: the age of 5 days after seeding (u1), age 10 days after seeding (u2), age 15 days after seeding (u3). The results showed that there was interactions between Arbuscular Mycorrhizal Fungi inoculants and seed age in the plant height 28 days after seedling (DAS) and DAS 42, Leaf Area Indeks (LAI) DAS 42 and DAS 49, Shout Root Ratio (SRR) DAS 35 and DAS 42, the number of tiller DAS 28, DAS 42 and DAS 56, and grain yield dry yield rice (Oryza sativa L.). There was no interaction between the effect of AMF inoculant and seed age on the degree of AMF infection and P uptake, plant height DAS 56 and DAS 70, LAI 35 and DAS 56, SRR DAS 49 and DAS 56. Mycorrhizal inoculation of 100 g kg-1 soil can increase the degree of AMF infection on the roots, but no significant effect on uptake of P, plant height DAS 56 and DAS 70, LAI 35 and DAS 56, SRR DAS 49 and DAS 56. Seed age did not significantly effect on the degree of AMF infection but the effect on P uptake, plant height DAS 56 and DAS 70, LAI 35 and DAS 56, SRR DAS 49 and DAS 56.